Small- and medium-sized enterprises and public procurement: A review of the UK coalition government's policies and their impact. (February 2018) - Loader, Kim
This paper examines the public procurement policy towards small- and medium-sized enterprises adopted by the UK coalition government during its five-year term of office from May 2010 to May 2015. First, it determines the policy instruments that have been implemented; second, it tracks policy development throughout the period and, third, it considers measurement and assessment of policy outcomes. Finally, it discusses the direction and nature of the policy development and considers implications for future policy development and further research. The paper found that the coalition government had actively and consistently pursued the policy of improving small- and medium-sized enterprise access to public procurement throughout the parliament. It determined that the coalition government had advanced the UK's intervention approach by its efforts in monitoring progress against some targets and, especially, by its increased use of regulation. As the legislation was introduced at the end of the period of office, it has been too early to consider how effectively the new requirements are being implemented, but the need to consider compliance and enforcement is identified. An aspirational target to spend 25% with small- and medium-sized enterprises was ostensibly met by central government departments but there is a need to develop better ways of measuring and collecting data. Finally, the evidence has revealed a low level of awareness of the initiatives amongst the target small- and medium-sized enterprise audience.